1967
DOI: 10.1152/ajplegacy.1967.213.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes of pH and of carbon dioxide tension on left ventricular performance

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
1

Year Published

1971
1971
2001
2001

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(30 citation statements)
references
References 0 publications
4
25
1
Order By: Relevance
“…The results in the present experiments are in agreement with the common notion that CO 2 exerts a deleterious effect upon the isolated heart (15,(17)(18)(19)(20)(21)(22).…”
Section: Discussionsupporting
confidence: 92%
“…The results in the present experiments are in agreement with the common notion that CO 2 exerts a deleterious effect upon the isolated heart (15,(17)(18)(19)(20)(21)(22).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, systemic pulmonary resistance. In contrast, hypocapnia-low pressure has been previously reported to decrease during alkalosis Pacoz, with a n~r m a l arterial pH-increased pulmonary in both humans (18) and animals (17,19). However, Rudolph pressure and pulmonary vascular resistance.…”
mentioning
confidence: 90%
“…[20][21][22][23][24] Walley et al reported that hypercapnic acidosis (PaCO 2 92 mmHg) decreases Ees by 19% in dogs anesthetized with fentanyl. 2 5 In contrast to previous studies in humans or dogs, hypercapnic acidosis caused bradycardia and reduced CO in our study of rabbits.…”
Section: Discussionmentioning
confidence: 99%